Relationship between ebv infection and expression of cellular proteins c-Myc, Bcl-2, and bax in gastric carcinomas - Lima, Marcos A. P.; Ferreira, Márcia V. P.; Barros, Marcos A. P.; Pardini, Maria I. M. C.; Ferrasi, Adriana C.; Mota, Rosa M. S.; Rabenhorst, Silvia H. B. (Wolters Kluwer, 2008)
BACKGROUND: Epstein-Barr virus (EBV) has been related to tumorigenesis in about 10% of all gastric carcinomas. Several studies have demonstrated strong evidence of its involvement in this process, but most of the mechanisms used by the virus to control this process are still unknown. Previous studies in vitro have indicated a relationship between the virus and some cellular genes involved in processes such as proliferation and apoptosis. OBJECTIVE: The aim of the present study was to investigate a possible EBV-induced tumorigenic pathway involving the cellular proteins Bcl-2, Bax, and c-Myc. STUDY DESIGN: One hundred patients of gastric carcinoma, obtained from 2 hospitals in Fortaleza, Brazil were assessed for the presence of EBV by in situ hybridization, for the expression of Bcl-2, Bax, and c-Myc (nuclear and cytoplasmic staining) proteins by immunohistochemistry techniques, and for the apoptotic index. RESULTS: EBV was detected in 8 (8%) patients showing strong staining situated in the nuclei of the tumor cells, 6 of them displaying a diffuse pattern, and 2 demonstrating a focal pattern of staining. The correlation with the immunohistochemistry results demonstrated that none of the EBV-positive cases exhibited Bcl-2 staining. On the other hand, Bax and c-Myc (nuclear) proteins demonstrated a significant positivity index and staining scores (labeling index and H-score) in the EBV-positive group; however, the values were lower than those obtained in the EBV-negative group, notably for c-Myc nuclear protein. In contrast, the cytoplasmic staining of c-Myc protein revealed slightly higher staining values in the EBV-positive group. The balance between Bcl-2 and Bax proteins demonstrated that the majority of the evaluated cases exhibited apoptosis orientation; however, in 62.5% of the EBV-positive cases neither protein was observed. The average apoptotic index was 4.58%, demonstrating a slightly lower average in the EBV-positive group. CONCLUSIONS: EBV is not related to the overexpression of Bcl-2 and c-Myc (nuclear) in gastric carcinomas; however, the results point to a possible EBV involvement with the transport mechanisms of the nuclear membrane, resulting in cytoplasmic c-Myc accumulation. The suppression of Bax expression could represent an alternative viral mechanism for inhibition of apoptosis. © 2008 by Lippincott Williams & Wilkins.
Keywords: Epstein-Barr virus; Gastric carcinoma; Tumorigenesis